Qualitative and mixed methods in public health - Padgett, Deborah K. (Thousand Oaks : SAGE, 2012)
'This text has a large emphasis on mixed methods, examples relating to health research, new exercises pertaining to health research, and an introduction on qualitative and mixed methods in public health. The book has an easy-to-read format and writing style and will also cover health focused research techniques, community participatory research, and will include boxed inserts pertaining to relevant real life examples'--Provided by publisher.
Machine generated contents note: Preface 1. Introduction 2. Choosing the Right Qualitative Approach(es) 3. Mixed Methods 4. Getting Started: Study Design and Sampling 5. Ethical Issues in Qualitative Research 6. Entering the Field and Conducting Observation 7. Interviewing and Use of Documents 8. Data Analysis and Interpretation 9. Strategies for Rigor 10. Telling the Story: Writing Up the Qualitative Study Appendix References Index About the Author .
Keywords: Public health; Qualitative research